2011
DOI: 10.3109/10253890.2011.578184
|View full text |Cite
|
Sign up to set email alerts
|

Behaviorally inhibited temperament is associated with severity of post-traumatic stress disorder symptoms and faster eyeblink conditioning in veterans

Abstract: Prior studies have sometimes demonstrated facilitated acquisition of classically-conditioned responses and/or resistance to extinction in post-traumatic stress disorder (PTSD). However, it is unclear whether these behaviors are acquired as a result of PTSD or exposure to trauma, or reflect pre-existing risk factors that confer vulnerability for PTSD. Here, we examined classical eyeblink conditioning and extinction in veterans self-assessed for current PTSD symptoms, exposure to combat, and the personality trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 49 publications
11
59
0
Order By: Relevance
“…Eyeblink sessions with excessive signal noise (loss of more than 10% of trials), incomplete session data (e.g., falling asleep), or that demonstrated a lack of a UR were discarded and not used from further analysis. Inspection of eyeblink conditioning sessions resulted in rejection of data from 45 participants, similar rejection rates were seen in previous human eyeblink studies [4][5][6]18]. …”
Section: Signal Processingsupporting
confidence: 79%
See 1 more Smart Citation
“…Eyeblink sessions with excessive signal noise (loss of more than 10% of trials), incomplete session data (e.g., falling asleep), or that demonstrated a lack of a UR were discarded and not used from further analysis. Inspection of eyeblink conditioning sessions resulted in rejection of data from 45 participants, similar rejection rates were seen in previous human eyeblink studies [4][5][6]18]. …”
Section: Signal Processingsupporting
confidence: 79%
“…One possibility is that anxious individuals are more sensitive to the cues and contingencies in their environments, resulting in faster learning and better performance on avoidance tasks. This theory is supported by the observation of individual differences in learning in both operant and classical conditioning avoidance paradigms [4][5][6]18,19]. Although operant paradigms may seem more suited to the high cognitive processes typically associated with avoidance, eyeblink classical conditioning is an established and reliable model for understanding human learning.…”
Section: Introductionmentioning
confidence: 92%
“…The CES (Keane et al, 1989) consists of 7 items that assesses frequency, duration, and amount of exposure to combat. Veterans with a total CES score <8 were classified as non-combat, while those scoring ≥8 were classified as having a history of exposure to combat, as done in previous studies (Ginsberg, Ayers, Burriss, & Powell, 2008; Myers et al, 2013; Myers, VanMeenen, McAuley, et al, 2012). The 16-item AMBI and 18-item RMBI (Gladstone & Parker, 2005) assess current (adult) and retrospective (childhood) behavioural inhibition (BI), defined as a tendency to withdraw from or avoid novel social and non-social situations; AMBI scores have been shown to correlate with measures of anxiety proneness (Gladstone & Parker, 2005; Gladstone, Parker, Mitchell, Wilhelm, & Malhi, 2005) and with self-reported PTSD symptoms (Myers, VanMeenen, McAuley, et al, 2012; Myers, VanMeenen, & Servatius, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…A physiologically mediated negative emotional bias may also underlie findings of (a) enhanced fear conditioning in PTSD , a possible preexisting vulnerability (Myers et al, 2012); (b) impaired safety signal learning Peri, Ben-Shakhar, Orr, & Shalev, 2000); and (c) deficits in fear extinction recall, thought to be an acquired characteristic (Milad et al, 2008). Interestingly, a common variation in the gene for an autoreceptor that restrains activation of the noradrenergic system (Neumeister et al, 2005) has been shown to be associated, even in healthy controls, with a negative emotional bias (Neumeister et al, 2006).…”
Section: Neurocognitive Function In Ptsdmentioning
confidence: 99%